AIRCRAFT FINANCING INDUSTRY: JURIDICAL ANALYSIS OF GUARANTEE AGREEMENT IN THE AIRCRAFT FINANCING INDUSTRY - Kuning, Fazahra Rimbani; Prabandari, Adya Paramita; Putrijanti, Aju (CREPIDO, 2023)
All humans require various supports to progress in life, particularly in Indonesia. People's mobility is required at a rapid pace due to the shape of Indonesia as an archipelago. The aviation industry is one of the supporting factors. Indonesians require the use of both domestic and international aircraft. As a result, massive procurement of aircraft fleets takes place. The airline requires financing to support the aviation sector as a capital-intensive and high-technology industry in its procurement. Every business activity must require collateral to prevent the parties from defaulting. As a result, the contents of this journal will explain the entire discussion of financing and collateral in accordance with applicable laws.